Pengaruh faktor Pengaruh faktor demografi, motif menabung, dan literasi keuangan syariah terhadap permintaan asuransi syariah, motif menabung, dan literasi keuangan syariah terhadap permintaan asuransi syariah - Meidiaswati, Harlina; Silvi, Mellyza (Jurnal Ilmu Manajemen, 2025)
A peaceful and prosperous retirement without financial problems is everyone's dream. This study aims to analyze the influence of financial knowledge and future orientation, mediated by external locus of control, on retirement planning behavior. The study used a quantitative approach. Testing was conducted on 321 respondents selected based on the following criteria: family financial managers with at least two years of work experience, a minimum family income of IDR 4,000,000 per month, and residing in Surabaya, Gresik, and Sidoarjo. Data were collected through questionnaires and analyzed using SEM PLS. The results indicate that financial knowledge and future orientation have a positive effect on retirement planning behavior, while external locus of control has a negative effect. These findings provide insight into the importance of improving financial knowledge through various means and enhancing future orientation through pension or retirement programs to improve retirement planning behavior. It is important to note the role of external locus of control, which weakens the influence of future orientation on retirement planning behavior.